A Method to Measure Standard Costs of Juvenile Justice Systems: The Example of Italy. (April 2022) - Ciappi, Silvio; Dalla Chiara, Elena; Padovani, Alessandro; Perali, Federico; Santagata, Barbara
This study proposes a standard costs method to evaluate the total direct costs of a juvenile justice system and applies it to the Italian case. The proposed cost-analysis method based on standard costs by offense-related groups illustrates how it can be implemented for improving the quality of management and cost monitoring. An illustrative cost-benefit analysis of the costs of juvenile justice in Italy shows that investments in rehabilitation programs are highly attractive even during a period of economic crisis and in very different regions.